Using medical expenditure panel survey data to explore the relationship between patient-centered medical homes and racial disparities in severe maternal morbidity outcomes - Curisa M Tucker; Nathaniel Bell; Cynthia F Corbett; Audrey Lyndon; Tisha M Felder (Women's Health, 2023)
Background: There are persistent racial/ethnic disparities in the occurrence of severe maternal morbidity. Patient-centered medical home care has the potential to address disparities in maternal outcomes. Objectives: To examine (1) the association between receiving patient-centered medical home care and severe maternal morbidity outcomes and (2) the interaction of race/ethnicity on patient-centered medical home status and severe maternal morbidity. Design/Methods: Using 2007 to 2016 data from the Medical Expenditures Panel Survey, we conducted a cross-sectional study to estimate the association between receipt of care from a patient-centered medical home and the occurrence of severe maternal morbidity, and racial-specific (White, Black, Asian, Other) relative risks of severe maternal morbidity. Our study used race as a proxy measure for exposure racism. We identified mothers (⩾15 years) who gave birth during the study period. We identified patient-centered medical home qualities using 11 Medical Expenditures Panel Survey questions and severe maternal morbidities using medical claims, and calculated generalized estimating equation models to estimate odds ratios of severe maternal morbidity and 95% confidence intervals. Results: Among all mothers who gave birth ( N  = 2801; representing 5,362,782 US lives), only 25% received some exposure patient-centered medical home care. Two percent experienced severe maternal morbidity, and this did not differ statistically ( p  = 0.11) by patient-centered medical home status. However, our findings suggest a 85% decrease in the risk of severe maternal morbidity among mothers who were defined as always attending a patient-centered medical home (odds ratios: 0.15; 95% confidence interval:0.01–1.87; p  = 0.14) and no difference in the risk of severe maternal morbidity among mothers who were defined as sometimes attending a patient-centered medical home (odds ratios: 1.00; 95% confidence interval:0.16–6.42; p  = 1.00). There was no overall interaction effect in the model between race and patient-centered medical home groups ( p  = 0.82), or ethnicity and patient-centered medical home groups ( p  = 0.62) on the severe maternal morbidity outcome. Conclusion: While the rate of severe maternal morbidity was similar to US rates, few mothers received care from a patient-centered medical home which may be due to underreporting. Future research should further investigate the potential for patient-centered medical home-based care to reduce odds of severe maternal morbidity across racial/ethnic groups.